Ways to Improve the Biological Activity and Fertivity of Rainfed Soils - Sattorovna, Sodiqova Gulchehra; o’g’li, Amirov Avazbek Kamiljon; qizi, Nurullayeva Bahora Sardor; qizi, Anorboyeva Mavsumaxon Abdurahmon; ug‘li, Temirbekov Adilbek Qutlibek (American Journal of Biodiversity, 2025)
Rainfed agriculture plays a critical role in global food security, yet these soils often face severe challenges, including nutrient depletion and low biological activity. This article explores sustainable strategies to enhance the fertility and microbial health of rainfed soils in the context of climate change 2025. Key methods discussed include the integration of green manures, conservation tillage, and advanced biological inoculation. The study highlights that improving soil organic carbon and promoting microbial diversity are essential for increasing water retention and crop yields. By adopting integrated soil fertility management (ISFM) practices, farmers can build resilient agroecosystems capable of withstanding environmental stressors.